Hospital Employees Organizational Citizenship Behavior: How the Correlation of Transformational Leadership, Job Satisfaction and Organizational Commitment ? - Novitasari, Dewiana (Journal of Industrial Engineering & Management Research, 2020)
The purpose of this study was to analyze Relationship between Transformational Leadership and Job Satisfaction, Relationship between Transformational Leadership and Organizational Commitmen Relationship between Transformational Leadership and OCB, Relationship between Job Satisfaction and Organization Commitment. The data is obtained through questionnaires distributed online through social media, the respondents of this study were 300 employees of the hospitals in Banten who were selected through simple random sampling method. Analysis of data processing using Structural Equation Modeling (SEM) with SmartPLS 4.0 software tools. The stages of PLS ​​analysis using smartpls 3 include 3 stages, namely: The outer model testing phase to test the validity & reliability of indicators and constructs, the Goodness of fit model testing phase to test the model’s predictive power and model feasibility, The inner model testing phase to test the significance the effect of exogenous variables on endogenous variables. From the research results obtained, it can be concluded as follows: (1) Transformational Leadership has a significant influence on job satisfaction. (2) Transformational Leadership significant effect on Organizational Commitment. (3) Transformational Leadership has a significant effect on OCB. (4) Job satisfaction has a significant effect on Organizational Commitment. (5) Organizational commitment has a significant effect on OCB